Adsorption of Pb(II) onto KCC-1 from aqueous solution: Isotherm and kinetic study - R., Hasan; Syahida Nasuha, Bukhari; Rohayu, Jusoh; Noor Sabrina, Ahmad Mutamim; Setiabudi, H. D. (Elsevier Ltd, 2018)
In this study, the removal of Pb(II) from aqueous solution using KCC-1 was investigated. BET and TEM revealed the favourable structure of KCC-1 which consists of fibrous morphology and high surface area. Batch adsorption experiment were performed to study the effect of contact time (40 – 160 min), effect of adsorbent dosage (0.5 – 5g/L), effect of initial concentration (50 – 400 mg/L) and effect of pH (2 – 8). The optimum condition was achieved at contact time of 80 min, adsorbent dosage of 4 g/L, initial concentration of 200 mg/L and pH of 6, with maximum removal of Pb(II) was 80.5%. The experimental data were analysed using Langmuir (Type 1, Type 2, Type 3 and Type 4), Freundlich, Temkin, and DubininRedushkevich isotherm models, and were found to follow Langmuir isotherm model with maximum adsorption capacity of 38.76 mg/g and high correlation coefficient (R2= 0.99), implying that the ongoing process is homogeneous in nature. Pseudo-first order, Pseudosecond order, Intra-particle diffusion and Elovich kinetic models were tested with the experimental data, and Pseudo-second order kinetic model was the best for the adsorption of Pb(II) onto KCC-1, indicating that the adsorption process most likely controlled by the chemisorption process and the rate of reaction is directly proportional to the number of active sites on the surface of adsorbent. The results obtained from this study revealed that KCC-1 had high potential for the adsorption of Pb(II) from aqueous solution.